Is Orthodontıc Treatment Success Affected By Personalıty Traıts Or Psycologıcal Status - Fulya Işık; Korkmaz Sayınsu; Göksu Trakyalı; Tülin Arun (Galenos Yayinevi, 2004)
A successful orthodontic treatment depends on a variety of factors. Cooperation of the patient during orthodontic treatment is a major determinant of a successful treatment result. Predicting patient cooperation could be helpful in anticipating problems that might arise during orthodontic treatment. In previous studies, it has been hypothesized that personality traits which can be determined by personality tests, and patient's psychological status might at least partly determine a patient's motivation for orthodontic treatment. However, other studies that used persponality variebles to predict adherence during orthodontic treatment have been unsuccessful in obtaining a clear answer or have found contradicting results. More research is needed to investigate the effect of patient's personality traits or psychological status on patient cooperation.